2012
DOI: 10.1214/11-aoas524
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and testing for spatially indexed curves with application to ionospheric and magnetic field trends

Abstract: We develop methodology for the estimation of the functional mean and the functional principal components when the functions form a spatial process. The data consist of curves X(s k ; t), t ∈ [0, T ], observed at spatial locations s1, s2, . . . , sN . We propose several methods, and evaluate them by means of a simulation study. Next, we develop a significance test for the correlation of two such functional spatial fields. After validating the finite sample performance of this test by means of a simulation study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 27 publications
(26 reference statements)
0
30
0
Order By: Relevance
“…Gromenko et al 97 proposed an iterative procedure for the estimation of the weights w n and the covariances C k . They showed that the weighted average 4.4 is a significantly better estimator than the usual sample average.…”
Section: Estimation Of the Mean Function And Of The Fpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gromenko et al 97 proposed an iterative procedure for the estimation of the weights w n and the covariances C k . They showed that the weighted average 4.4 is a significantly better estimator than the usual sample average.…”
Section: Estimation Of the Mean Function And Of The Fpcsmentioning
confidence: 99%
“…Estimation of the v j in the spatial setting involves issues similar to those related in the estimation of the mean function μ, but the notation and approaches are more complex. They are discussed in Gromenko et al 97 and Hörmann and Kokoszka 98 .…”
Section: Estimation Of the Fpcsmentioning
confidence: 99%
“…In this section, we propose an extension of the methodology for the estimation of the mean function and the FPCs that are introduced by Gromenko et al. (2012).…”
Section: Estimation Of the Mean And Covariance Functionsmentioning
confidence: 99%
“…If the conclusion does not depend on d, we can be confident that it is correct. This approach has been used in applied research, see Gromenko et al (2012) for a recent analysis of this type. The second approach, would be to let d increase with the sample size N, and derive a test statistic based on the limit.…”
Section: Introductionmentioning
confidence: 99%